2017
DOI: 10.1186/s12940-017-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations of genetic variation in CASP3 gene with noise-induced hearing loss in a Chinese population: a case–control study

Abstract: BackgroundNoise-induced hearing loss (NIHL) is a complex disease caused by environmental and genetic risk factors. This study explored the relationship between the genetic variations in the CASP gene and the risk of developing NIHL among Chinese workers exposed to occupational noise.MethodsA case–control study of 272 NIHL workers and 272 normal-hearing workers matched for age, sex and years of noise exposure was conducted. Fifteen single-nucleotide polymorphisms (SNP) in the CASP1, CASP3, CASP4, CASP5, CASP6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…The binaural high-frequency hearing threshold which was greater than 25 dB was noise-induced hearing loss [21], otherwise is non-binary high-frequency hearing loss.…”
Section: Hearing Test and Hearing Loss Diagnosismentioning
confidence: 99%
“…The binaural high-frequency hearing threshold which was greater than 25 dB was noise-induced hearing loss [21], otherwise is non-binary high-frequency hearing loss.…”
Section: Hearing Test and Hearing Loss Diagnosismentioning
confidence: 99%
“…e mutation of the binding site of the target gene of miRNAs will affect the biosynthesis or biological function of miRNAs, which will lead to the disorder of cellular function and eventually result in the occurrence of diseases. SNPs can have a profound impact on miRNA function, including transcription, maturation, and target specificity [32], and it can also affect the occurrence of NIHL [33]. Recent studies have shown that SNPrs11077 in XPO5 gene is related to the risk of esophageal cancer, colorectal cancer, and renal cancer [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…e A>C polymorphism of XPO5 gene will reduce the risk of CAD (coronary artery disease), which may be due to the influence on the expression of mature miRNAs and their gene function [37]. At the same time, functional SNPs in miRNA biogenetic pathway genes have been confirmed to be related to the increased risk of NIHL [33,38]. Based on all the above studies, we analyzed the relationship between the functional sites of XPO5 of miRNA processing gene and NIHL, and its effect on miRNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common sensory organ defect in the world is hearing loss [24]. Hearing can be impaired directly by high-intensity and long-term noise exposure, eventually leading to NIHL [25].…”
Section: Discussionmentioning
confidence: 99%